RELATION THE TREATMENT OF BREAST AT A PERIOD OF ANTENATAL WITH VELOCITY OF SECRETION OF PRIMIPARA MOTHER’S MILK AFTER CHILDBIRTH - Astari, Asti Melani; Djuminah, Djuminah (University of Muhammadiyah Malang, 2012)
Good nutrition in infancy foster optimal growth and development. Human milk contains all the nutritional needs for the first 6 months of life. Breastfed exclusively for the first 6 months of life but that needed by correct management or efforts, so that every mother can suckle their baby, which one of them by doing the treatment of breast at a period of antenatal. The purpose of this research is to know about the existence of relation the treatment of breast at a period of antenatal with velocity of secretion of primipara motherâ€™s milk after childbirth in RSU Dr Saiful Anwar Malang. This study is descriptive research using cross sectional approach. The existence of relation the treatment of breast at a period of antenatal with velocity of secretion of primipara motherâ€™s milk after childbirth (post partum) tested by using chi-square tests, spearman correlation and odds ratio. The findings were identified that most velocity of secretion primipara motherâ€™s milk after childbirth most showing pertained secretion quickly or less than 24 hours (53,3%). From examination result with Chi-Square test (ï£2 = 8,571 dan p = 0,003) showing that there is relation between the treatment of breast at a period of antenatal with velocity of secretion of primipara motherâ€™s milk after childbirth in RSU Dr Saiful Anwar Malang. The result of correlation test (r = 0,535 and p = 0, 002), show that existence of treatment of breast at a period of antenatal, will make the secretion of primipara motherâ€™s milk after childbirth (post partum) tend to quicker or less than 24 hour with opportunity (odds ratio) 11 times quicker better than the mother which do not do the treatment of breast at a period of antenatal.